Tri-tert-butanolamine as an organic promoter in nucleophilic fluorination - Shinde, Sandip S.; Khonde, Nilesh; Kumar, P. (ChemistrySelect, 2017)
Tri-tert-butanol amine acts as promoter with alkali metal salts in the nucleophilic fluorination of alkylsulfonates. It significantly enhances the reactivity of alkali metal salts with minimum formation of side-products (alkene, ether, and alcohol) com-pared to other catalysts in fluorination reaction. The synergism of tert-alcohol and amine moiety plays a pivotal role in fluorination.

Effect of tert-alcohol functional imidazolium salts on oligomerization and fibrillization of amyloid beta (1-42) peptide - Said, Madhukar S.; Navale, Govinda R.; Yadav, Ashok; Khonde, Nilesh; Shinde, Sandip S.; Jha, Anjali (Biophysical Chemistry, 2020)
Imidazolium based IL's has gained vast interest in developing biological applications. Oligomerization and fibrillization of amyloid beta (1-42) peptide are mainly responsible for the extra-neuronal deposition of amyloid fibrils in neurodegenerative disorders like Alzheimer's disease (AD). Here, we report an effect of tert-BuOH-functional imidazolium ILs on oligomerization and fibrillization of amyloid beta (1-42) Peptide in vitro. In this study, a series of these [alkyl-(t)OHim][OMs] ILs with methyl sulphonate counter anion by varying alkyl chains were used. Among the seven protic ILs, four showed strong binding and inhibition activity for the formation of amyloid beta (1-42) aggregation by using Thioflavin T fluorescence binding assay. The secondary structural analysis of the peptide, pre-incubated with active ILs shows the loss of ordered beta-sheet amyloid structure. The longer alkyl chain ILs showed that an increased in amyloid binding and hence an inhibition effect on amyloid aggregation was enhanced. Thus, we propose that ILs could be presented as potential candidates for therapeutic intervention against Alzheimer's disease (AD).
Keywords: Aggregation; Amyloid beta (1-42) peptide; Biofilm inhibitor; Imidazolium ionic liquid